Methods for Structuring Knowledge in Online Encyclopedias - Irina Kobozeva; Natalia Loukachevitch; Maria Panich; Fedor Sadkovsky; Eugeny Raevsky (Современные информационные технологии и IT-образование)
Currently, several online encyclopedias are being developed in Russian. The Great Russian Encyclopedia (GRE), the Russian-language encyclopedia Ruwiki are being created. The “Ark of Knowledge” project is being developed at Lomonosov Moscow State University, which is considered as a repository of knowledge in various formats, as well as a base for preparing articles for the Great Russian Encyclopedia Internet-portal. Modern electronic encyclopedias include hundreds of thousands of articles. This requires the use of special means of structuring knowledge to improve the efficiency of information search and user navigation through the pages of the encyclopedia. Hyperlinks are a generally accepted method of navigation between pages in online resources. Wikipedia, the largest and most famous Internet encyclopedia, has a developed system (hierarchy) of categories and subcategories, which unite Wikipedia pages into thematic groups. Similar categorization is used in a Russian Wikipedia-like resource - Ruwiki. The Great Russian Encyclopedia uses the system of facet classification and keywords. The Lomonosov Moscow State University "Ark of Knowledge" system assumes the use of ontologies for structuring knowledge, i.e. formalized descriptions of subject areas in the form of a system of classes and relationships between them. Ontologies are supposed to improve the efficiency of information access, both for users and for automatic processing by software agents. The article considers the features of each approach of knowledge structuring. In particular, the problems of the extensive Wikipedia category system created by users, which reflect typical difficulties in formalizing knowledge description, will be presented. The problems of using ontologies for knowledge categorization will be considered using Wikidata as an example.